2022
DOI: 10.1111/acel.13622
|View full text |Cite
|
Sign up to set email alerts
|

Defective mitophagy in aged macrophages promotes mitochondrial DNA cytosolic leakage to activate STING signaling during liver sterile inflammation

Abstract: Macrophage‐stimulator of interferon genes (STING) signaling mediated sterile inflammation has been implicated in various age‐related diseases. However, whether and how macrophage mitochondrial DNA (mtDNA) regulates STING signaling in aged macrophages remains largely unknown. We found that hypoxia‐reoxygenation (HR) induced STING activation in macrophages by triggering the release of macrophage mtDNA into the cytosol. Aging promoted the cytosolic leakage of macrophage mtDNA and enhanced STING activation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…The molecular interactions of T. polium ’s major compounds with these key receptors, which are targeted in liver therapy, were studied. Both CYP and STING are considered key areas of focus for liver diseases, and thus constituted excellent targets for liver medication [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular interactions of T. polium ’s major compounds with these key receptors, which are targeted in liver therapy, were studied. Both CYP and STING are considered key areas of focus for liver diseases, and thus constituted excellent targets for liver medication [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that impaired mitophagy increases ROS-mediated hepatocyte pyroptosis to promote the extracellular release of mtDNA during acute liver injury (23). We also found that defective mitophagy ux in aged macrophages aggravates liver IR injury by promoting cytosolic mtDNA release and STING-NLRP3 activation (12). Failure to clear defective mitochondria via mitophagy drives autoimmune responses through mtDNA-dependent cGAS-STING activation (43).…”
mentioning
confidence: 94%
“…(8-10) We previously found that mitochondrial DNA (mtDNA) from ischemia-stressed hepatocytes activates macrophage cGAS-STING signaling to promote nucleotide-binding domain and leucine-rich repeat containing protein 3 (NLRP3)-mediated in ammatory IR injury in aged livers. (11,12) The role of MLKL in regulating liver IR injury has recently been reported. (13) Inhibition of MLKL suppresses ischemia-induced hepatocyte necroptosis in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the double-stranded DNA (ds DNA) sensor cyclic-GMP-AMP synthase (cGAS) and the downstream stimulator of interferon genes (STING) pathways (cGAS/STING) is emerging as an important regulator and therapeutic target of sterile inflammation and its unwarranted effects (Decout et al 2021 ; Huang et al 2020 ). Cytosolic dsDNA is recognized as a universal DAMP that acts as a ligand to activate cGAS/STING pathway, and the stress-induced cytosolic leakage of mitochondrial DNA (mt DNA), including in immune cells such as macrophages, has been implicated in augmented inflamm-aging that contributes to immunosenescence (Atayik and Çakatay 2022b ; Conte et al 2020 ; Lv et al 2022 ; Zhong et al 2022 ). Accumulating evidence suggests that inflamm-aging is essentially an age-dependent remodeling of the immune response due to an imbalance between anti-inflammatory and pro-inflammatory networks.…”
Section: Introductionmentioning
confidence: 99%